2005
DOI: 10.4143/crt.2005.37.6.339
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Second-line Single Docetaxel (75 mg/m2) Therapy in Advanced Non-Small Cell Lung Cancer Patients who were Previously Treated with Platinum-based Chemotherapy

Abstract: Purpose: W hen used in the second-line setting, singleagent chemotherapy has produced response rates of more than 10% or median survival times greater than 4 months. W e studied the safety and efficacy of using second-line single docetaxel (75 mg/m 2 ) for advanced NSCLC patients who were previously treated with platinum-based chemotherapy in Korea.Materials and Methods: Thirty-three patients with advanced NSCLC received chemotherapy from May 2002 to January 2005. W e retrospectively reviewed the charts of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, the PFS benefit was only 3 months for this group of patients [ 25 27 ]. Previous studies have also shown a low ORR ranging between 9 and 18% for patients who received docetaxel as second-line regimen after progression from first-line platinum-based chemotherapy [ 25 28 ]. Thus, an alternative second-line regimen that could improve the clinical and survival outcomes of this patient population after progression from chemotherapy remains an unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…However, the PFS benefit was only 3 months for this group of patients [ 25 27 ]. Previous studies have also shown a low ORR ranging between 9 and 18% for patients who received docetaxel as second-line regimen after progression from first-line platinum-based chemotherapy [ 25 28 ]. Thus, an alternative second-line regimen that could improve the clinical and survival outcomes of this patient population after progression from chemotherapy remains an unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…This trial established the superiority of docetaxel, at the intermediate dose of 75 mg/m 2 , for the response rate, the time to progression and the overall survival of the study patients. Shim et al reported that 75 mg/m 2 of docetaxel monotherapy every 3 week was also effective in a Korean population with a response rate of 18.2% and a median survival time of 11 months 16) .…”
Section: Discussionmentioning
confidence: 99%
“…During the initial introduction of docetaxel, it was routinely administered once every 3 weeks. However, although docetaxel was effective salvage treatment in patients previously treated with platinum-based chemotherapy, hematological toxicity was substantial with the 3-week treatment schedule; grade 3 or 4 neutropenia was observed in 54-67% of patients treated with a 75 mg/m 2 dose of docetaxel ( 3 , 4 , 8 ). Even at a 60 mg/m 2 dose, grade 3 or 4 neutropenia developed in more than 80% of patients in a Japanese trial ( 9 ).…”
Section: Introductionmentioning
confidence: 99%